2015
DOI: 10.1128/iai.00142-15
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Lung Inflammation Reduces Tissue Invasion and Enhances Survival from Pulmonary Pneumococcal Infection in Mice, Which Correlates with Increased Expression of Transforming Growth Factor β1 and SiglecF low Alveolar Macrophages

Abstract: Asthma is generally thought to confer an increased risk for invasive pneumococcal disease (IPD) in humans. However, recent reports suggest that mortality rates from IPD are unaffected in patients with asthma and that chronic obstructive pulmonary disease (COPD), a condition similar to asthma, protects against the development of complicated pneumonia. To clarify the effects of asthma on the subsequent susceptibility to pneumococcal infection, ovalbumin (OVA)-induced allergic lung inflammation (ALI) was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…We have previously reported that alveolar macrophages play an important role in early bacterial clearance (4, 28, 29). Indeed, depletion of alveolar macrophages during coinfection of AAD mice significantly reduced survival (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that alveolar macrophages play an important role in early bacterial clearance (4, 28, 29). Indeed, depletion of alveolar macrophages during coinfection of AAD mice significantly reduced survival (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-b is abundantly produced during AAI and is dominantly present in post-AAI lungs. 35 TGF-b could suppress GM-CSF secretion by lung cells and hence inhibit post-AAI rAM maturation. Furthermore, a study by Sawada et al 36 reported the inhibitory effect of IL-4 on GM-CSF production.…”
Section: Discussionmentioning
confidence: 99%
“…Wildly conflicting results have been published on the impact of asthma on S. pneumoniae infection in mice. Intraperitoneally, OVA-sensitized mice have been reported to display reduced ( 74 ), similar ( 75 ), or enhanced ( 76 , 77 ) susceptibility to infection. The discrepancies between these results may be connected with the serotype of S. pneumoniae used, the sanitary level of the mice, or a delay between infection and asthma challenge.…”
Section: Discussionmentioning
confidence: 99%